Comparative Analysis of Risk Assessment Practices in Public and Private Procurement in Nigeria - D. N Okereke (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
Procurement activities constitute a significant portion of organizational expenditure in Nigeria, accounting for approximately 10-15% of GDP in the public sector and 60-70% of operational expenses in the private sector. Despite the enactment of the Public Procurement Act 2007, public procurement continues to face challenges including cost overruns, delays, and quality issues, suggesting deficiencies in risk assessment practices. This comparative study examines risk assessment practices in public and private procurement in Nigeria using a mixed-methods approach. Data was collected through structured questionnaires administered to 198 public sector respondents from the Federal Road Maintenance Agency and 87 private sector respondents from Autograph Construction Company Ltd, achieving an overall response rate of 92.2%. The study found significant differences between sectors: governance-related risks (political interference, corruption) were more prevalent in public procurement, while the private sector demonstrated superior risk assessment capabilities with 83.9% having formal frameworks compared to 33.8% in the public sector. Private sector organizations showed significantly higher institutional capacity (M=3.87 vs. M=2.54, p<0.001) and better procurement outcomes, with 43.7% achieving 90-100% budget compliance versus only 6.1% in the public sector. Strong positive correlations were established between effective risk assessment and procurement outcomes (r=0.701, p<0.001). The study recommends establishing dedicated risk management units, implementing formal risk assessment frameworks, accelerating technology adoption, and strengthening regulatory oversight to improve procurement risk management in both sectors.